Safety and efficacy of Axtra® XAP 104 TPT (endo‐1, 4‐xylanase, protease and alpha‐amylase) as a feed additive for chickens for fattening, laying hens and minor poultry species. (29th June 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Axtra ® XAP 104 TPT as a zootechnical feed additive (digestibility enhancers) for poultry species. The additive contains three enzyme activities (endo‐1, 4‐beta‐xylanase, protease and alpha‐amylase) produced by three different genetically modified strains. Viable cells and recombinant DNA of the strains producing the protease and amylase were not detected in the final product. Owing to the insufficient data, uncertainty remained on the presence in the additive of viable cells of the strain producing the xylanase. The results obtained in the genotoxicity and subchronic oral toxicity studies performed with the three fermentation products did not indicate safety concerns resulting from the fermentation products used in the formulation/manufacturing. However, uncertainties remain on the suitability of the test item used in the studies conducted with the xylanase; therefore, the Panel was not in the position to conclude on the toxicological potential of AXTRA ® XAP 104 TPT. Consequently, the Panel could not conclude on the safety of the additive for the target species, consumers and users. Owing to the uncertainty on the presence of viable cells of one of the production strains in the additive, the Panel could not conclude on the safety for the environment. The FEEDAP Panel concluded that AXTRA ® XAP 104 TPT is efficacious in chickens for fattening, chickens reared for laying and minor poultry species up to the point of lay at the level of 2, 000 U xylanase, 200 U amylase and 4, 000 U protease per kg feed. Owing to the lack of sufficient data, the Panel could not conclude on the efficacy of the additive for laying hens.